2011
DOI: 10.1007/s10552-011-9784-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of marital status on stage and survival of prostate cancer patients treated with radical prostatectomy: a population-based study

Abstract: Being SDW significantly increased the risk of more advanced stage at RP. Following surgery, SDW men portended to a higher CSM and ACM rate than married men. Consequently, these individuals may benefit from a more focused health care throughout the natural history of their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 40 publications
6
54
0
1
Order By: Relevance
“…7 Conversely, SDW patients were more likely to harbor locally advanced PCa at RP (OR 1.1, 95% CI 1.0-1.2, P = 0.001). It is noteworthy that Abdollah et al were not able to investigate whether SDW patients were actually single or lived with a partner.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…7 Conversely, SDW patients were more likely to harbor locally advanced PCa at RP (OR 1.1, 95% CI 1.0-1.2, P = 0.001). It is noteworthy that Abdollah et al were not able to investigate whether SDW patients were actually single or lived with a partner.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Abdollah et al showed no significant differences between married and never married individuals (HR 1.0), whereas Tyson et al recorded an increased risk of cancer-specific mortality within unmarried individuals (HR 1.4, P < 0.001). 7,8 Third, the study population consisted of just 9% single patients. Differences within reported rates of single patients might be caused by different definitions of marital status in use, different regions (USA vs Europe), timespans and health resources (center of excellence vs community hospitals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, having a partner is known to afford PCa specific benefits [15,25] and, in general, married men are reported to be more likely to use preventative health care services [26].…”
Section: Prostate Cancer Masculinities and Gender Relationsmentioning
confidence: 99%
“…Marital status has been associated with outcomes in several cancer sites [42][43][44]. The potentially significant impact that social support can have on breast cancer detection, treatment, and survival has been well described [45][46][47].…”
Section: Discussionmentioning
confidence: 99%